Chemical disinfectants and antiseptics. Quantitative non- porous surface test for the evaluation of virucidal activity of chemical disinfectants and antiseptics used in the veterinary area. Test method and requirements. Phase2, step2. (27th November 2019) - British Standards Institution,
No abstract available